Monitoramento da coluna total de ozônio e a ocorrência de eventos de influência do buraco de ozônio antártico sobre o sul do Brasil - Peres, Lucas Vaz (2016)
The present PhD thesis analyzes the results obtained from the Total Ozone Column (TOC) monitoring conducted in the Southern Space Observatory - SSO (29.26 ° S, 53.48 °W and 488 m altitude) between 1992 and 2014 by three successive Brewer spectrophotometers (# 081, # 056 and # 167). First, the Brewer measurements were compared with TOMS (Total Ozone Mapping Spectrometer) and OMI (Ozone Monitoring Instrument) satellites obtaining excellent agreement. In addition, was determined that the seasonal TOC variability is dominated by the annual cycle, with a minimum of ~ 260 DU in April and a maximum of ~ 295 DU in September. The Quasi-Biennial Oscillation (QBO) is the main mode of interannual variability being approximately in antiphase with the QBO index. Next, 58 events of the influence of the Antarctic Ozone Hole on the SSO station was identificate in the period between 2005 and 2014. This events occurred on average 5.8 ± 3.51 times per year, with a mean reduction of TOC by Brewer' of -7.04 ± 2.97% and by OMI of -7.66 ± 3.11 respectively. Analyzing the ozone profiles from AURA/MLS (Microwave Limb Sounder) satellite, the average isentropic level for maximum reduction is 644.68 ± 158.59 K, with a mean reduction of 15.39 ± 6.47%, being October the month of greatest occurrence (18 events). The events were separated into three categories: TOC intensity reduction, height of the ozone reduction lamina in AURA/MLS satellite and the dynamic characteristic of Polar Filament or Polar Tongue through the application of Dybal (Dynamical Barrier Localization) code in the potential vorticity (PV) fields from MIMOSA (Modélisation Isentrope du transport Mésoéchelle de l'Ozone Stratosphérique par Advection) model. The events with a dynamic feature of Polar Tongue (20,68%) occurred more frequently in October, with medium intensity and in the medium stratosphere, while events of dynamic characteristic of Polar Filament (79,31%) occurred more frequently in September, also with medium intensity and in the medium stratosphere.